TNF‐α Upregulates Fgl2 Expression in Rat Myocardial Ischemia/Reperfusion Injury. (9th August 2013) - Jia, Peng; Wang, Jue; Wang, Li; Chen, Xin; Chen, Yu; Li, Wen‐Zhu; Long, Rui; Chen, Jian; Shu, Yan‐Wen; Liu, Kun; Wang, Zhao‐Hui
Abstract Objective Proinflammatory cytokine TNF‐α during MI/R injury has been studied extensively. However, how TNF‐α induces microvascular dysfunction in MI/R is still unclear. This study investigates whether TNF‐α regulates fibrinogen‐like protein 2 (fgl2) expression, a procoagulant resulting in the formation of fibrin‐rich microthrombus in MI/R injury. Methods and Results Microthrombosis, TNF‐α and fgl2 expression were assessed in rats with MI/R injury. The effect of TNF‐α on fgl2 expression and fgl2 prothrombinase activity was investigated in CMECs, then CMECs were pretreated with selective inhibitors of NF‐κB and p38 MAPK pathways. TNF‐α and fgl2 expression were both upregulated in MI/R group. When neutralization of TNF‐α, fgl2 expression was decreased in vivo. Fgl2 expression was upregulated in CMECs exposed to TNF‐α. Accordingly, the ability of thrombin generation was increased in CMECs. Besides, TNF‐α‐induced fgl2 expression in the cells was suppressed by NF‐κB inhibitor PDTC and/or p38 MAPK inhibitor SB203580. Conclusion TNF‐α upregulates fgl2 expression via activation of NF‐kB and p38 MAPK in CMECs. TNF‐α‐induced flg2 in CMECs mediates the formation of fibrin‐rich microthrombus, which may be one of the mechanisms of microvascular dysfunction or obstruction due to MI/R injury.